Handbook of international law - Aust, Anthony (Cambridge University, 2013)
A concise account of international law by an experienced practitioner, this book explains how states and international organisations, especially the United Nations, make and use international law. The nature of international law and its fundamental concepts and principles are described. The difference and relationship between various areas of international law which are often misunderstood (such as diplomatic and state immunity and human rights and international humanitarian law) are clearly explained. The essence of new specialist areas of international law relating to the environment, human rights and terrorism is discussed." "Aust's clear and accessible style makes the subject understandable to non-international lawyers, non-lawyers and students. Abundant references are provided to sources and other materials, including authoritative and useful websites.